Safety assessment of intraparenchymal central nervous system biopsies: Single institution healthcare value review. (May 2021) - Mazur-Hart, David J.; Yaghi, Nasser K.; Goh, Jo Ling; Lin, Yimo; Han, Seunggu
Highlights: Stereotactic brain biopsies have a very low rate of morbidity and mortality. Brain biopsy patients can recover on a neurosurgical ward; ICU care is not needed. Eliminating postoperative head CT and ICU admission will decrease healthcare costs. Abstract: The study objective was to evaluate a single institution experience with adult stereotactic intracranial biopsies and review any projected cost savings as a result of bypassing intensive care unit (ICU) admission and limited routine head computed tomography (CT). The authors retrospectively reviewed all stereotactic intracranial biopsies performed at a single institution between February 2012 and March 2019. Primary data collection included ICU length of stay (LOS), hospital LOS, ICU interventions, need for reoperation, and CT use. Secondarily, location of lesion, postoperative hematoma, neurological deficit, pathology, and preoperative coagulopathy data were collected. There were 97 biopsy cases (63% male). Average age, ICU LOS, and total hospital stay were 58.9 years (range; 21–92 years), 2.3 days (range; 0–40 days), and 8.8 days (range 1–115 days), respectively. Seventy-five (75 of 97) patients received a postoperative head CT. No patients required medical or surgical intervention for complications related to biopsy. Eight patients required transfer from the ward to the ICU (none directly related to biopsy). Nine patients transferred directly to the ward postoperatively (none required transfer to ICU). Of the patients who did not receive CT or went directly to the ward, none had extended LOS or required transfer to ICU for neurosurgical concerns. Eliminating routine head CT and ICU admission translates to approximately 584, 971 in direct cost savings in 89 cases without a postoperative ICU requirement. These practice changes would save patients' significant hospitalization costs, decrease healthcare expenditures, and allow for more appropriate hospital resource use.